1989
DOI: 10.1002/jsfa.2740470405
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding tannic acid and kidney bean (Phaseolus vulgaris) on the intestinal absorption of D‐galactose and L‐leucine in chickens

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Monteleone et al (2004) had studied the astringency intensity rating of TA using human subjects and had reported a steep increase in the intensity of perceived sensation of astringency with an increase in the concentration of TA from 0.32 to 1.63 g/L. However, it has also been suggested that a slightly astringent taste may increase the palatability of feed and stimulate feed intake (Gupta and Haslam, 1980;Santidrian and Marzo, 1989). The results of our study suggest that TA may have reduced the palatability only for a short duration (during days 0 to 14 as observed in the current study), and pigs may adapt to the presence of TA in the diet (during days 15 to 28 the ADFI was comparable among treatments).…”
Section: Discussionmentioning
confidence: 97%
“…Monteleone et al (2004) had studied the astringency intensity rating of TA using human subjects and had reported a steep increase in the intensity of perceived sensation of astringency with an increase in the concentration of TA from 0.32 to 1.63 g/L. However, it has also been suggested that a slightly astringent taste may increase the palatability of feed and stimulate feed intake (Gupta and Haslam, 1980;Santidrian and Marzo, 1989). The results of our study suggest that TA may have reduced the palatability only for a short duration (during days 0 to 14 as observed in the current study), and pigs may adapt to the presence of TA in the diet (during days 15 to 28 the ADFI was comparable among treatments).…”
Section: Discussionmentioning
confidence: 97%
“…It has been demonstrated that inclusion of feed ingredients containing tannins resulted in undesirable physiological and biochemical effects (Armstrong et al, 1974;Smulikowska et al, 2001) including growth inhibition, negative nitrogen balances, reduced intestinal absorption of sugars and amino acids, reduced immune response, and increased protein catabolism (Santidrian, 1981;Santidrian and Marzo, 1989;Marzo et al, 2002). However, with better understanding of the chemical composition and biological activity of tannins (Mueller-Harvey, 2006), tannin is now known to play a beneficial antioxidant role, preventing lipid peroxidation (Laughton et al, 1991;Morel et al, 1993;Caraceni et al, 1997;Lopes et al, 1999;Rajalakshmi et al, 2001;Glahn et al, 2002) reported that at 0.5% inclusion rate, chestnut tannins had positive effects on carcass characteristics, meat quality, lipid oxidation and fatty acid composition in rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…We also investigated the effect of TA on cecal fermentation which plays a role in absorption. In Experiment 1, to set the optimum dose of Fe, male Sprague-Dawley rats (weighing 70-90 g) after acclimatization were fed with different levels of dietary Fe (5,10,20,30 and 35 mg/ kg). We observed that the hematocrit (Ht), serum Fe concentration and transferrin saturation (%) were each reduced in those rats fed less than 20 mg/kg Fe in a dose-dependant manner.…”
mentioning
confidence: 99%